PENGARUH MANAJEMEN SDM BERKELANJUTAN, BUDAYA ORGANISASI RAMAH LINGKUNGAN, DAN KEPEMIMPINAN TRANSFORMASIONAL HIJAU TERHADAP KINERJA LINGKUNGAN PERUSAHAAN DI KOTA SURABAYA - Rahayu Mardikaningsih (Universitas Mahendradatta, 2025)
This study aims to examine the influence of sustainable human resourcemanagement (HRM), green organizational culture, and green transformationalleadership on the environmental performance of companies in Surabaya City. Aquantitative approach was used with a survey of 100 corporate HR managersselected through purposive sampling. Data analysis was conducted using multiplelinear regression to evaluate the relationship between variables. The results showedthat the three independent variables had a significant influence on the company'senvironmental performance. Sustainable HRM contributes through managementthat supports sustainability, while green organizational culture strengthenscollective commitment to sustainability goals. Green transformational leadershipproved to be an important catalyst that drives innovation and pro-environmental behavior at all levels of the organization. These findings not only reinforcesustainability theory in academic literature, but also provide practical guidance forcompanies to improve their environmental performance. This research highlightsthe importance of an integrated strategy to create significant sustainability impactin the local context of Surabaya City.